2015
DOI: 10.1016/j.plefa.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of modifying dietary LA and ALA intakes on omega-3 long chain polyunsaturated fatty acid (n-3 LCPUFA) status in human adults: A systematic review and commentary

Abstract: The effect of modifying dietary LA and ALA intakes on omega-3 long chain polyunsaturated fatty acid (n-3 LCPUFA) status in human adults: a systematic review and commentary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 44 publications
5
48
2
Order By: Relevance
“…This is in line with the observations of the systematic review of Wood et al 26 who state that a combination of a decrease of LA and a simultaneous increase of ALA intake is most effective in improving the n3 PUFA status.…”
Section: Rbc Fatty Acid Concentrationssupporting
confidence: 91%
See 3 more Smart Citations
“…This is in line with the observations of the systematic review of Wood et al 26 who state that a combination of a decrease of LA and a simultaneous increase of ALA intake is most effective in improving the n3 PUFA status.…”
Section: Rbc Fatty Acid Concentrationssupporting
confidence: 91%
“…However, the timeframe of 14 days may be too short to observe significant changes in DHA concentrations. Wood et al 26 concluded that ALA supplementation studies with decreased LA intake -as our study -were able to increase DHA concentrations. Our results cannot confirm this observation, on the one hand possibly due to the short intervention time and on the other hand also due to the high ALA dose in this study.…”
Section: Rbc Fatty Acid Concentrationssupporting
confidence: 61%
See 2 more Smart Citations
“…The latter may influence eicosanoid signaling, which has been reported to be associated with the development and progression of CRC (49). In addition, contrary to common beliefs, the current evidence does not support that an increase in ALA intake can enhance DHA synthesis (50). In fact, recently, it was reported that a higher ALA intake was associated with decreased tissue DHA concentrations (51), because of the feedback inhibition that controls DHA synthesis (52).…”
Section: Discussioncontrasting
confidence: 83%